The On-ground, Hybrid, Online, and Flipped Classroom: A Comparative Study of Didactic Methods in L2 Teaching - Bachelor, Jeremy W. (2019)
The purpose of this study is to compare and contrast on-ground, hybrid, online, and flipped teaching techniques in the L2 classroom as to determine which delivery method best promotes student learning, target language use, and language spontaneity among students. Data was collected for three semesters at a college in the Midwestern region of the United States from different sections of the same introductory-level Spanish course. The differences between the class sections was the delivery method (one for each type of the aforementioned methods). A sample group of 53 participants were compared with the on-ground/traditional class section final and oral exams and compared with the on-ground/traditional section using unpaired t tests. Each of the class instructors maintained a journal to document qualitative classroom experiences. The study concludes that no one group performed statistically better than the other group on the oral exams. There were no statistically significant differences on the final exams, except with the online class group which performed worse. The delivery method selected should be based on student, community, and departmental needs. However, instructor journals noted greater target language use in the flipped and hybrid sections.